Supervised exercise therapy versus usual care for patellofemoral pain syndrome: an open label randomised controlled trial - van Linschoten, R (BMJ Publishing Group Ltd., 2009)
Objective To assess the effectiveness of supervised exercise therapy compared with usual care with respect to recovery, pain, and function in patients with patellofemoral pain syndrome. Design Open label randomised controlled trial. Setting General practice and sport physician practice. Participants Patients with a new episode of patellofemoral pain syndrome recruited by their general practitioner or sport physician. Interventions The intervention group received a standardised exercise programme for 6 weeks tailored to individual performance and supervised by a physical therapist, and were instructed to practise the tailored exercises at home for 3 months. The control group were assigned usual care, which comprised a “wait and see” approach of rest during periods of pain and refraining from pain provoking activities. Both the intervention group and the control group received written information about patellofemoral pain syndrome and general instructions for home exercises. Main outcome measures The primary outcomes were self reported recovery (7 point Likert scale), pain at rest and pain on activity (0-10 point numerical rating scale), and function (0-100 point Kujala patellofemoral score) at 3 months and 12 months follow-up. Results A total of 131 participants were included in the study: 65 in the intervention group and 66 in the control group. After 3 months, the intervention group showed better outcomes than the control group with regard to pain at rest (adjusted difference −1.07, 95% confidence interval −1.92 to −0.22; effect size 0.47), pain on activity (−1.00, −1.91 to −0.08; 0.45), and function (4.92, 0.14 to 9.72; 0.34). At 12 months, the intervention group continued to show better outcomes than the control group with regard to pain (adjusted difference in pain at rest −1.29, −2.16 to −0.42; effect size 0.56; pain on activity −1.19, −2.22 to −0.16; effect size 0.54), but not function (4.52, −0.73 to 9.76). A higher proportion of patients in the exercise group than in the control group reported recovery (41.9% v 35.0% at 3 months and 62.1% v 50.8% at 12 months), although the differences in self reported recovery between the two groups were not statistically significant. Predefined subgroup analyses revealed that patients recruited by sport physicians (n=30) did not benefit from the intervention, whereas those recruited by general practitioners (n=101) showed significant and clinically relevant differences in pain and function in favour of the intervention group. Conclusion Supervised exercise therapy resulted in less pain and better function at short term and long term follow-up compared with usual care in patients with patellofemoral pain syndrome in general practice. Exercise therapy did not produce a significant difference in the rate of self reported recovery. Trial registration ISRCTN83938749.